Asymmetric hydrogenation of γ‐branched allylamines for the efficient synthesis of γ‐chirogenic amines. Issue 2 (5th August 2021) - Zhang, Jian; Chen, Tiantian; Wang, Yuanhao; Zhou, Fengfan; Zhang, Zhenfeng; Gridnev, Ilya D.; Zhang, Wanbin
Abstract : Abstract: The efficient construction of γ ‐chirogenic amines has been realized via asymmetric hydrogenation of γ ‐branched N ‐phthaloyl allylamines by using a bisphosphine‐Rh catalyst bearing a large bite angle. The desired products possessing different γ ‐substituents were obtained in quantitative yields and with excellent enantioselectivities (up to >99% ee). This protocol provides a practical method for the preparation of γ ‐chirogenic amine derivatives such as the famous antidepressant drug Fluoxetine (up to 50000 S/C). The mechanistic calculations show an unusual P‐Rh‐P trans ‐chelating pattern and a weak interaction‐promoted activation mode which are completely different from the traditional cis ‐chelating pattern and coordination‐promoted activation mode in metal‐catalyzed hydrogenations. Key points: Novel methodology of asymmetric hydrogenation was developed for efficient synthesis of γ‐chirogenic amines. New synthetic route was developed for the well‐known antidepressant drug Fluoxetine. Unusual mechanism information was found in the bidentate bisphosphine‐Rh‐catalyzed hydrogenation. Abstract : The challenging asymmetric hydrogenation of γ‐branched allylamines has been realized by using a bisphosphine‐Rh catalyst bearing a large bite angle to generate applicable γ‐chirogenic amines with excellent enantioselectivity (up to >99% ee) and high efficiency (up to 50000 S/C). A nearly linear P‐Rh‐P coordination pattern and a weak interaction‐promoted substrate activation mode, both of which have never been reported in metal‐catalyzed hydrogenations, have been demonstrated according to the mechanistic calculations.